Kajian Makna Leksikal Puisi Di Negeri Amplop Karya KH. Mustofa Bisri - Najibul - Mahbub; Ika Septiana (Universitas PGRI Semarang, 2023)
This research aims to discuss the lexical meaning contained in the poem 'Di Negeri Envelope' by KH Mustofa Bisri. Lexical meaning is a word that stands alone and is independent of context. Lexical meaning has an important role in the use of language because it can connect between language, words and sentences that exist inside and outside the language. This lexical meaning cannot be changed or is already in the dictionary. In this research, the stanzas of poetry become the study of lexical meaning analysis. This research method uses a qualitative descriptive method with data collection techniques in the form of simak catat with steps to collect data then categorized and then analyzed in the form of tables and descriptions. Poetry is created through the process of selecting diction, so the right selection will create meaning. That is the reason the author analyzes the lexical meaning in the poem 'In the Land of Envelopes' by KH Mustofa Bisri. It is hoped that this research can provide benefits for the world of Indonesian language and literature education.Keywords: Lexical meaning, poetry, Analysis, Gus Mus, Envelope